Thrombolytic Activity Test of Spider Plant Leaf Extract (Chlorophytum Spp.) - Siska Zafrida; Hartini H; Ignatius Yulianto; Melsa kharunnisa (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Cardiovascular disease (CVD) is a disorder of the heart and blood vessels and remains the leading cause of death worldwide. Atherosclerosis and thrombosis are major contributors to CVD. Thrombolytic agents such as urokinase, streptokinase, and nattokinase are effective in dissolving blood clots; however, their prolonged use may cause adverse effects and high treatment costs. Therefore, the development of safer and more affordable natural thrombolytic agents is necessary. This study aimed to evaluate the in vitro thrombolytic activity of ethanol extract from spider plant leaves (Chlorophytum spp.). The study employed a post-test only control group experimental design using extract concentrations of 0.5%, 1%, and 2%, with nattokinase as the positive control and distilled water as the negative control. Phytochemical screening revealed the presence of flavonoids, saponins, and tannins in the extract. The thrombolytic activity increased with increasing extract concentration. The ethanol extract demonstrated clot lysis percentages of 2.8%, 4.2%, and 5.5% at concentrations of 0.5%, 1%, and 2%, respectively. Although its thrombolytic activity was lower than that of the positive control, the extract showed concentration-dependent thrombolytic potential. These findings suggest that spider plant (Chlorophytum spp.) leaves possess bioactive compounds with thrombolytic properties and may serve as a promising natural source for the development of alternative thrombolytic agents. Further studies, including isolation of active compounds and in vivo evaluation, are recommended.